ANALISIS LAPORAN ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PADA PT ASTRA INTERNATIONAL TBK PERIODE 2019-2023 - Ambar Putri, Dewinta; Hendra, Dede (Journal of Research and Publication Innovation, 2024)
The purpose of the study is to determine and analyze the cash flow report in assessing financial performance at PT Astra International Tbk for the 2019-2023 period. The type of research conducted by the author is quantitative descriptive research. The research data comes from the financial statements of PT Astra International Tbk for the 2019-2023 period, including the balance sheet, profit and loss and cash flow. The data analysis technique used in this study is the descriptive method. The conclusion of the study shows that the results of the calculation of the operating cash flow ratio analysis for the 2019-2023 period show poor fluctuations, indicating a liquidity risk that can disrupt the payment of short-term financial obligations. However, the analysis of cash coverage to current liabilities in that time period is quite good, indicating the company's ability to meet financial obligations in the short term. Although fluctuating, the analysis of total debt and cash coverage to interest also shows a relatively strong financial condition. Despite the variations, the company has a good ability to pay debt and interest with cash flow from its normal operations.